2020
DOI: 10.1186/s12911-020-01361-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hospitalization following psychiatric crisis care using machine learning

Abstract: Background Accurate prediction models for whether patients on the verge of a psychiatric criseis need hospitalization are lacking and machine learning methods may help improve the accuracy of psychiatric hospitalization prediction models. In this paper we evaluate the accuracy of ten machine learning algorithms, including the generalized linear model (GLM/logistic regression) to predict psychiatric hospitalization in the first 12 months after a psychiatric crisis care contact. We also evaluate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Our proposed model performed an accuracy of 90.4%, an AUC of 0.959, a PPV of 0.933 and a NPV of 0.929 including 35 features. This result is better than the one found by [4], that found an AUC=0.774 including 39 features, and the one found by [5], that found an AUC=0.7. Our result is also better than the one found by [7], that found an AUC=0.813 in the validation cohort using 48 features.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Our proposed model performed an accuracy of 90.4%, an AUC of 0.959, a PPV of 0.933 and a NPV of 0.929 including 35 features. This result is better than the one found by [4], that found an AUC=0.774 including 39 features, and the one found by [5], that found an AUC=0.7. Our result is also better than the one found by [7], that found an AUC=0.813 in the validation cohort using 48 features.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies have shown promising results when applying machine learning algorithms to predict hospitalization [4], [5]. Blankers, van der Post and Dekker [4] found Gradient Boosting to be the best performing algorithm (Area Under the Curve (AUC)=0.774) including 39 variables related to patients' socio-demographics, clinical characteristics, and previous mental health care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our XGBoost models only achieved a minimum improvement compared with logistic regression in predicting hospitalization and ED visit, consistent with previous studies. 9,14,40,41 Interestingly, our models performed better than models used by Care Compare based on various metrics of performance. 5 There are multiple reasons why this may have occurred.…”
Section: Discussionmentioning
confidence: 85%
“…Our model performances exceed many existing predictive models, which reported AUC of around 0.7. 12,[39][40][41] One strength of our model is the inclusion of detailed resident-level predictors from MDS, 4 which gave us more power to predict hospital transfers. Our XGBoost models only achieved a minimum improvement compared with logistic regression in predicting hospitalization and ED visit, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%